Placental volumes measured by 3-dimensional ultrasonography in normal pregnancies from 12 to 40 weeks' gestation - De Paula, Carla Fagundes Silva (2008)
Objective. The purpose of this study was to construct nomograms of placental volumes according to gestational age and estimated fetal weight. Methods. From March to November 2007, placental volumes were prospectively measured by ultrasonography in 295 normal pregnancies from 12 to 40 weeks' gestation and correlated with gestational age and estimated fetal weight. Inclusion criteria were healthy women, singleton pregnancies with normal fetal morphologic characteristics on ultrasonography, and confirmed gestational age by first-trimester ultrasonography. Results. The mean placental volume ranged from 83 cm3 at 12 weeks to 427.7 cm3 at 40 weeks. Linear regression yielded the following formula for the expected placental volumes (ePV) according to gestational age (GA): ePV (cm3) = -64.68 + 12.31 x GA (r = 0.572; P < .001). Placental volumes also varied according to estimated fetal weight (EFW), and the following mathematical equation was also obtained by linear regression: ePV = 94.19 + 0.09 x EFW (r = 0.505; P < 0.001). Conclusions. Nomograms of placental volumes according to gestational age and estimated fetal weight were constructed, generating reference values. © 2008 by the American Institute of Ultrasound in Medicine.